Overhauling the Effect of Surface Sterilization on Analysis of Endophytes in Tea Plants - Yu, Yueer; Chen, Zimeng; Xie, Hengtong; Feng, Xiaoxiao; Wang, Yuefei; Xu, Ping (Frontiers in Plant Science, 2022)
Increasing evidence shows that plant Endophytes play a crucial role in the fitness and productivity of hosts. Surface sterilization is an indispensable process before high-throughput sequencing (HTS) and tissue separation of plant endophytes, but its potential impact on the composition and diversity of endophytes has rarely been investigated. In the present work, the influence of sodium hypochlorite (NaClO) on the diversity of endophytic bacteria and fungi in leaves and stems of tea plants was investigated. We found that the diversity of bacterial endophytes was significantly affected by the concentration of NaClO as well as the pretreatment time. Pretreatment with 0.5% NaClO for 8 min and 2.0% NaClO for 3 min were suitable for the tea plant leaves and stems, respectively, but the effects of NaClO on the diversity of fungal endophytes were limited according to the results from HTS. Regardless of NaClO sterilization, most of the endophytes in tissues, such as the dominant taxa, could not be Isolated by using the regular culture-dependent approaches. Collectively, our results demonstrated that the pretreatment with NaClO should be modified to precisely understand the diversity of endophytes from different tissues of tea plants and also indicate that more attention should be paid to establish specific culture-dependent protocols for the isolation of plant endophytes.